The Effectiveness of Digital Waste Management Application Gamification in Fostering Environmental Awareness and Operational System Sustainability - Rahayu Mardikaningsih; Mila Hariani; Reny Nuraini (Bulletin of Science, Technology and Society, 2026)
The rapid growth of urban waste volume demands innovative environmental governance based on information technology and active public participation. This study aims to analyze the effectiveness of gamification mechanics in mobile waste management applications in transforming social behavior and ecological awareness, while formulating operational management strategies for waste processing to sustain public participation. A sequential explanatory mixed-methods approach was applied through a combination of quantitative surveys among active application users and qualitative exploration via in-depth interviews and field observations. The findings reveal that interactive elements such as point accumulation, achievement badges, and communal leaderboards significantly increase household waste separation consistency by fostering intrinsic motivation and establishing new social norms. Conversely, the sustainability of citizen participation strongly depends on the reliability of physical collection systems, Global Positioning System-based fleet route optimization, recycling supply chain efficiency, and the stability of incentive financing schemes. This study concludes that integrating user-friendly digital game design with reliable field logistics is the primary key to achieving sustainable urban environmental governance driven by community involvement.